Calculating with light using a chip-scale all-optical abacus - J. Feldmann; M. Stegmaier; N. Gruhler; C. Ríos; H. Bhaskaran; C. D. Wright; W. H. P. Pernice (Nature Communications, 2017)
Computing approaches in the optical domain would allow for ultra-fast signaling and ultra-high bandwidth capabilities. Here, Feldmann et al. demonstrate a photonic abacus, which provides multistate compute-and store operation by integrating phase-change materials with nanophotonic chips.